2019
DOI: 10.1111/tmi.13195
|View full text |Cite
|
Sign up to set email alerts
|

The willingness to participate in biomedical research involving human beings in low‐ and middle‐income countries: a systematic review

Abstract: ObjectivesTo systematically review reasons for the willingness to participate in biomedical human subjects research in low‐ and middle‐income countries (LMICs).MethodsFive databases were systematically searched for articles published between 2000 and 2017 containing the domain of ‘human subjects research’ in ‘LMICs’ and determinant ‘reasons for (non)participation’. Reasons mentioned were extracted, ranked and results narratively described.ResultsNinety‐four articles were included, 44 qualitative and 50 mixed‐m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
30
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(39 citation statements)
references
References 111 publications
(544 reference statements)
4
30
0
Order By: Relevance
“…For many participants, trust in the healthcare providers was a significant element in decision-making about research participation. The role of trust regarding research participation has been observed in multiple settings [16,[27][28][29]. In other contexts, it seems that mistrust is a more important element that needs to be addressed in communities where research takes place [30,31].…”
Section: Discussionmentioning
confidence: 99%
“…For many participants, trust in the healthcare providers was a significant element in decision-making about research participation. The role of trust regarding research participation has been observed in multiple settings [16,[27][28][29]. In other contexts, it seems that mistrust is a more important element that needs to be addressed in communities where research takes place [30,31].…”
Section: Discussionmentioning
confidence: 99%
“…8 Additionally, sociodemographic factors, including education, income, and religion, may influence participants' decision to provide their consent and to participate in biomedical research. [9][10][11][12] There have been few studies that have evaluated awareness of participants about biomedical research and factors affecting their willingness to participate in biomedical research in the Middle East, 13,14 and none has been conducted within the Jordanian community. Accordingly, the aim of the current study was to assess the knowledge and awareness of public in Jordan about biomedical research and to determine factors associated with their participation in various types of biomedical research studies.…”
Section: Introductionmentioning
confidence: 99%
“…This cascade can reduce willingness to participate in research, and undermine trust in biomedical science. It also falls below recommended standards for participant research (Barrett et al, 2020;Browne et al, 2019).…”
Section: Introductionmentioning
confidence: 89%